Ischaemia-free liver transplantation in humans: a first-in-human trial - Zhiyong Guo, M.D., Ph.D; Qiang Zhao, M.D., Ph.D; Shanzhou Huang, M.D., Ph.D; Changjun Huang, M.D; Dongping Wang, M.D., Ph.D; Lu Yang, M.D., Ph.D; Jian Zhang, M.Sc; Maogen Chen, M.D., Ph.D; Linwei Wu, M.D., Ph.D; Zhiheng Zhang, M.D; Zebin Zhu, M.D., Ph.D; Linhe Wang, M.D; et al. (Elsevier, 2021)
Summary: Background Ischaemia-reperfusion injury is considered an inevitable component of organ transplantation, compromising organ quality and outcomes. Although several treatments have been proposed, none has avoided graft ischaemia and its detrimental consequences.Methods Ischaemia-free liver transplantation (IFLT) comprises surgical techniques enabling continuous oxygenated blood supply to the liver of brain-dead donor during procurement, preservation, and implantation using normothermic machine perfusion technology. In this non-randomised study, 38 donor livers were transplanted using IFLT and compared to 130 conventional liver transplants (CLT).Findings Two recipients (5•3%) in the IFLT group experienced early allograft dysfunction, compared to 50•0% in patients receiving conventional transplants (absolute risk difference, 44•8%; 95% confidence interval, 33•6-55•9%). Recipients of IFLT had significantly reduced median (IQR) peak aspartate aminotransferase levels within the first week compared to CLT recipients (365, 238-697 vs 1445, 791-3244 U/L, p<0•001); likewise, median total bilirubin levels on day 7 were significantly lower (2•34, 1•39-4•09 mg/dL) in the IFLT group than in the CLT group (5•10, 1•90-11•65 mg/dL) (p<0•001). Moreover, IFLT recipients had a shorter median intensive care unit stay (1•48, 0•75-2•00 vs 1•81, 1•00-4•58 days, p=0•006). Both one-month recipient (97•4% vs 90•8%, p=0•302) and graft survival (97.4% vs 90•0%, p=0•195) were better for IFLT than CLT, albeit differences were not statistically significant. Subgroup analysis showed that the extended criteria donor livers transplanted using the IFLT technique yielded faster post-transplant recovery than did the standard criteria donor livers transplanted using the conventional approach.Interpretation IFLT provides a novel approach that may improve outcomes, and allow the successful utilisation of extended criteria livers.Funding This study was funded by National Natural Science Foundation of China, Guangdong Provincial Key Laboratory Construction Projection on Organ Donation and Transplant Immunology, and Guangdong Provincial international Cooperation Base of Science and Technology.Panel: Research in context